Monophasic action potential duration alternans after abrupt shortening of the cardiac cycle in humans - Kazumasa Sonoda, MD (Journal of Arrhythmia, 2014)
Background: Action potential alternans may be important in causing ventricular arrhythmias. Methods and results: We recorded monophasic action potentials from the right ventricular endocardium in patients with persistent atrial fibrillation who underwent internal atrial defibrillation during rapid ventricular pacing. In 3 of 45 patients, monophasic action potential duration alternans was observed at a pacing cycle length ≤350 ms. Conclusion: Action potential alternans is not a rare phenomenon (6.6%) in humans.